(untitled) (Research, Society and Development, 2022)
The aim of this study was to know the perceptions of parents in relation to the diagnosis of down syndrome and access to health services. A descriptive study was conducted with a qualitative approach, conducted with nine parents of children with down syndrome enrolled in the Association of Parents and Friends of The Exceptional (APAE). Data were obtained through semi-structured interviews and analyzed in order to unsee out thematic categories. Results: The results showed two thematic categories: "Parents’ perception of the diagnosis of down syndrome and obstacles in ensuring access to health care". Parents demonstrate ambivalence about satisfaction in the professional approach at the time of diagnosis, pointing out satisfaction and also dissatisfaction with the professional’s approach. It is evident the need for further studies providing the construction of an adequate approach posture of the professional through the diagnosis of down syndrome and an innovative access to health with quality and efficacy.